Development of instant ginger (Zingiber Officinale Roscoe) tea and its consumer acceptance - Cervantes, Alicia
The preparation of instant ginger tea or "salabat" in tea bags was studied. The effects of varying temperatures in the cabinet drying of ginger whether peeled or unpeeled was determined relative to retention of the essential flavor properties of ginger. The particle size most conducive to dissolution of ginger flavor in hot water and the minimum quantity of ginger powder packed in a tea bag to produce the desired flavor of "salabat" in a cup were determined. For the purpose, fresh Hawaiian ginger was soaked and washed in tap water, drained and then divided into two lots. One lot was peeled and the other lot was left unpeeled. Both lots were sliced into 1/8 inch julienne strips. The first lot was divided into three batches, each batch being dried at 120°F, 140°F and 160°F respectively. The hydrated ginger slices were then powdered into three different particle sizes and were subjected to physico-chemical tests. On the basis of the results of theses tests, the drying temperature for the unpeeled lot was determined. The dehydrated ginger slices from the second lo was powdered to the sample particle size as the peeled lot. The powder was then packed in tea bags and were subjected to sensory evaluation for flavor, aroma, and general acceptability. A acceptability test was conducted on the samples rated with the highest scores by the panel. Results in the physico-chemical test and the sensory evaluation of the ginger tea indicated that although drying temperature did not significantly affect the quality of the ginger tea, a drying temperature of 140°F was deemed optimum for ginger. Phyico-chemical tests revealed no significant difference in the qualities of ginger powder prepared from peeled or unpeeled ginger. Subjective tests, however, indicated that he powder of the unpeeled ginger gave a more desirable drink in terms of flavor, aroma and general acceptability. Of the three particle sizes studied that which passes through No.80 at a quantity level of 1.5g. was found to give a drink with the desirable flavor of "salabat".